How Strategic Agility Impacts The Business Sustainability Of The Next Generation Family Business: Case Study Of Ampalu Raya Padang Restaurant - Baihaaqi, Muhammad Jahfal; Yulihasri; Laura Syahrul (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This research aims to investigate how strategic agility affects business sustainability in next-generation family businesses, with a focus on Ampalu Raya Restaurant in Padang. The method used is a qualitative approach, where data is collected through in-depth interviews with owners, and employees and secondary data analysis. The sample consisted of three informants representing owners and staff located in Padang City. The variables studied include strategic agility, business sustainability, and the factors influencing both. The main findings show that strategic agility, as measured by strategic sensitivity, resource fluidity, and leadership unity, contributes positively to business sustainability, as evidenced by increased revenue and product quality. The research also highlights the importance of integrating sustainability practices in succession planning. The implications of the findings show relevance to business policies and practices and open up opportunities for further research on the impact of digitalization and innovation in the family culinary sector.